URANG TUO PASIA PEMERSATU NELAYAN DAN PELESTARI SUMBERDAYA KELAUTAN - Ferawati Ferawati (LIPI Press, 2005)
This study is about Urang Tuo Pasia, â€œThe Fishermen Leader and Ocean Resources Conserverâ€. Urang Tuo Pasia is both a institution and a chief in traditional costums of a fishermen community in Bungus-Teluk Kabung, Padang, West Sumatra. Instead of Urang Tuo Pasia, he is also called as Angku (â€œfatherâ€) or Tuo Pasia (â€œthe old fishermanâ€). The aim of the study is to find out the role of Urang Tuo Pasia in the problems of the integration among the fishermen and the conservation of the sea natural resources. This reveals as an important thing since from the historical perspective, many manuscripts note that Urang Tuo Pasia could have had outstanding role in solving the problems encountered by the local fishermen. The method used in this research is qualitative one. It is supported by multidimensional approaches to sharpen the analysis. They come from the field of anthropology, sociology, economics, and politics. From the various data found and analyzed, this research concludes hat theroleof Urang Tuo Pasia is running into stagnation. However, it local wisdom still remain.